Det härliga livet: Om njutning i Are Waerlands hälsolära - Elebro, Sandra (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
Are Waerland was a famous health prophet in the 1930’s and 40’s. His message was that all diseases and sicknesses were caused by the unhealthy lifestyles of Modern Man. To reach out with his doctrine he emphasized how pleasant his diet was and how glorious the life as a Waerlandist would be. When Waerland described the tastes, looks and smells of vegetables he wanted to turn people into a totally new diet. But the enjoyment his followers experienced had more to do with the feeling of succeeding with keeping the strict diet and lifestyle rather than with the pleasures of eating the prescribed food. But inside the narrow frames they found great opportunities to enjoy life — all according to the gospel of Waerland. My study focuses on the ways in which enjoyment as an emotion was discussed and played out in the Waerland movement.